2022
DOI: 10.1038/s41598-022-22198-w
|View full text |Cite
|
Sign up to set email alerts
|

Environmental RNA as a Tool for Marine Community Biodiversity Assessments

Abstract: Microscopic organisms are often overlooked in traditional diversity assessments due to the difficulty of identifying them based on morphology. Metabarcoding is a method for rapidly identifying organisms where Environmental DNA (eDNA) is used as a template. However, legacy DNA is problematically detected from organisms no longer in the environment during sampling. Environmental RNA (eRNA), which is only produced by living organisms, can also be collected from environmental samples and used for metabarcoding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 55 publications
1
25
0
1
Order By: Relevance
“…Unlike DNA, RNA is only produced for genes that are actively being transcribed, making it a useful tool for understanding the “real time” status of the organisms. Recent studies reported that the degradation of eRNA for some genes was slower than previously expected. eRNA has been detected for a wide range of aquatic species, including fish, ,, water fleas, , polychaetas, ,, mussels, ascidians, algae, and others . Also, eRNA has been detected for both mitochondrial and nuclear genes ,, and for several microRNAs .…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Unlike DNA, RNA is only produced for genes that are actively being transcribed, making it a useful tool for understanding the “real time” status of the organisms. Recent studies reported that the degradation of eRNA for some genes was slower than previously expected. eRNA has been detected for a wide range of aquatic species, including fish, ,, water fleas, , polychaetas, ,, mussels, ascidians, algae, and others . Also, eRNA has been detected for both mitochondrial and nuclear genes ,, and for several microRNAs .…”
Section: Introductionmentioning
confidence: 86%
“…Recent studies reported that the degradation of eRNA for some genes was slower than previously expected. 14−17 eRNA has been detected for a wide range of aquatic species, including fish, 16,18,19 water fleas, 17,20 polychaetas, 14,21,22 mussels, 15 ascidians, 14 algae, 23 and others. 22 Also, eRNA has been detected for both mitochondrial and nuclear genes 15,16,18 and for several microRNAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of eRNA ecology and fate within an aquatic environment and particularly in marine environments, is still in its infancy, and the lack of data on its basic ecological properties, such as common forms present in the environment (e.g., particulate, cellular or extracellular), persistence and degradation mechanism, means its biomonitoring performance remains unclear (Jo, Tsuri, et al, 2022). However, recent proof‐of‐concept studies have demonstrated that eRNA, combined with eDNA, is a promising tool for biodiversity assessment and marine biosecurity programs (Giroux et al, 2022; Laroche et al, 2018; Miyata et al, 2021; Veilleux et al, 2021; Yates et al, 2021). Environmental RNA's faster decay rate allows for inferences about the presence or absence of species in “real‐time,” enabling better identification of living and viable organisms/assemblages, increased sensitivity, reducing false positives and enabling the estimate of species abundance with more precision (Bowers et al, 2021; Farrell et al, 2021; Kagzi et al, 2022; Miyata et al, 2021; Qian et al, 2022; Wood et al, 2020).…”
Section: Guidelines On Establishing Decay Ratesmentioning
confidence: 99%
“…However, recent proof-of-concept studies have demonstrated that eRNA, combined with eDNA, is a promising tool for biodiversity assessment and marine biosecurity programs (Giroux et al, 2022;Laroche et al, 2018;Miyata et al, 2021;Veilleux et al, 2021;Yates et al, 2021). Environmental RNA's faster decay rate allows for inferences about the presence or absence of species in "real-time," enabling better identification of living and viable organisms/assemblages, increased sensitivity, reducing false positives and enabling the estimate of species abundance with more precision (Bowers et al, 2021;Farrell et al, 2021;Kagzi et al, 2022;Miyata et al, 2021;Qian et al, 2022;Wood et al, 2020).…”
Section: Recommendation One: Improve Under Standing Of Environmental ...mentioning
confidence: 99%